30-Year Experience With 22 Cases of Malignant Transformation Arising From Ovarian Mature Cystic Teratoma: A Rare Disease - Li, Yan; Qin, Meng; Shan, Ying; Wu, Huan-wen; Liu, Xiao-ding; Yin, Jie; Gu, Yu; Wang, Wei; Wang, Yong-xue; Chen, Jia-yu; Ma, Li; Jin, Ying; et al. (Frontiers in Oncology, 2022)
Methods: This retrospective study included patients with ovarian MCTs at Peking Union Medical College Hospital (PUMCH) during 1990.01-2020.12. When the pathologic histology was MT-MCT, detailed information was collected. Results: Overall, 7229 ovarian MCT patients and 22 patients with MT-MCT were enrolled. The rate of malignant transformation of all ovarian MCTs was 0.30%. Most patients with MT-MCT were 51 (21-75) years old, and the tumor mass size was 10 (3-30) cm. The typical clinical symptoms were mainly abdominal pain and distension. The levels of tumor markers were elevated on preoperative examination. Early diagnosis could be made by ultrasonic examination, pelvic enhanced MRI and CT. Most patients underwent debulking surgery and adjuvant chemotherapy. The most common histological type to exhibit malignant transformation was squamous cell carcinoma (59.1%), followed by adenocarcinoma (13.6%), carcinoid (9.1%), and borderline tumor (18.2%). The 5-year RFS and OS rates were 54.5% and 81.8%, respectively. Patients with FIGO stage I had the best RFS (P=0.047) and OS (P=0.018), followed by those with FIGO stage II-IV. Conclusion: MT-MCTs mainly occur in elderly females, are rare and have a poor prognosis. Advanced FIGO stage is a risk factor for survival. Although there is no standard treatment, cytoreductive debulking surgery and adjuvant chemotherapy could be considered. Perimenopausal and menopausal women with MCT should receive surgical treatment.